2004
DOI: 10.1167/4.10.5
|View full text |Cite
|
Sign up to set email alerts
|

The perceptual and cognitive distractor-previewing effect

Abstract: The time it takes to respond to an odd-colored target (e.g., a red diamond among green diamonds) is reduced when distractor-colored items in an appropriate geometric configuration (e.g., multiple red diamonds) are previewed in a preceding trial. B. A. Goolsby and S. Suzuki (2002) suggested that this phenomenon, the distractor-previewing effect, occurs because target saliency is increased by global adaptation to the previewed distractors. The present study tested and extended this idea with visual search experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
41
2
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 20 publications
2
41
2
1
Order By: Relevance
“…A consistent finding from this work is that search efficiency increases with target repetition (see Kristjánsson, 2006, for a review). More pertinent to the present discussion, such repetition benefits have also been reported recently for distractors (Ariga & Kawahara, 2004;Geyer, Müller, & Krummenacher, 2006;Kristjáns-son & Driver, 2008;Lleras, Kawahara, Wan, & Ariga, 2008). For example, Kristjánsson and Driver found faster search times when a given distractor type appeared on successive trials than when the distractors differed.…”
supporting
confidence: 81%
“…A consistent finding from this work is that search efficiency increases with target repetition (see Kristjánsson, 2006, for a review). More pertinent to the present discussion, such repetition benefits have also been reported recently for distractors (Ariga & Kawahara, 2004;Geyer, Müller, & Krummenacher, 2006;Kristjáns-son & Driver, 2008;Lleras, Kawahara, Wan, & Ariga, 2008). For example, Kristjánsson and Driver found faster search times when a given distractor type appeared on successive trials than when the distractors differed.…”
supporting
confidence: 81%
“…Hence, if an irrelevant prime distractor is repeated as a target in the subsequent probe display (distractor-to-target repetition), responses are typically slowed down, because the internal stimulus representation still suffers from inhibition (Neill, 1977;Tipper, 1985). Similar negative effects of distractor-to-target repetitions have also been reported in the visual search literature (socalled "distractor previewing effects," "role reversal effects," or "switching effects"; Ariga & Kawahara, 2004;Lamy, Antebi, Aviani, & Carmel, 2008;Levinthal & Lleras, 2008;Yashar & Lamy, 2010).…”
mentioning
confidence: 79%
“…However, there are also intertrial effects driven by distractors, known as the colorsalience aftereffect (Goolsby, Grabowecky, & Suzuki, 2005) and the distractor preview effect (Ariga & Kawahara, 2004;Lleras, Kawahara, Wan, & Ariga, 2008). In those studies, the color oddball pop-out task trials were interspersed with target-absent trials, which consisted of three same-colored items (i.e., all distractors).…”
Section: Discussionmentioning
confidence: 99%
“…For example, repetition of a big red target coactivates features for red and big. If a small red target appears after the repetition of a big red target, red carries weakly over to the next trial, if at all, because the other feature (size) mismatches; the targets across these two trials are et al showed that the distractor preview aftereffect is present only if the task requires focal attention (see also Goolsby et al, 2005, andKawahara, 2004, for a perceptual-suppression account of this aftereffect). The difference between the present results and these aftereffects might be that the present results showed a positive attentional bias to the attended item and the aftereffect tasks show a negative attentional bias to the attended item.…”
Section: Discussionmentioning
confidence: 99%